The Pengaruh Free Cash Flow dan Struktur Kepemilikan Saham terhadap Kebijakan Utang pada Perusahaan Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia tahun 2013 - 2017 - Mariska Mariska (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
This study aims to determine the effect of free cash flow and share ownership structure on debt policy in automotive and component companies listed in Indonesia Stock Exchange from 2013 until 2017. The research method used is quantitative method by collecting data and then reprocessing it with the 22 version of the SPSS program. The sample drawn by purposive sampling and fulfill sample selection criterion. The results of the study show that free cash flow and managerial ownership has negative and insignificant effect on debt policy, while institutional ownership has negative and significant effect on debt policy. Simultaneously shows that free cash flow, managerial ownership and institutional ownership affect debt policy.